Photoinduced superconducting nanowires in GdBa2Cu3O6.5 films - Decca, R.S.; Drew, H.D.; Maiorov, B.; Guimpel, J.; Osquiguil, E.; Guimpel, Julio (AIP Publishing, 1998)
Fil: Maiorov, B. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina